2016
DOI: 10.1007/s10048-016-0481-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic fitness and selection intensity in a population affected with high-incidence spinocerebellar ataxia type 1

Abstract: Spinocerebellar ataxia type 1 (SCA1) is the major and likely the only type of autosomal dominant cerebellar ataxia in the Sakha (Yakut) people of Eastern Siberia. The prevalence rate of SCA1 has doubled over the past 21 years peaking at 46 cases per 100,000 rural population. The age at death correlates closely with the number of CAG triplet repeats in the mutant ATXN1 gene (r = −0.81); most patients with low-medium (39–55) repeat numbers survived until the end of reproductive age. The number of CAG repeats exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A large variance exists in the number of individuals with ADCAs that are confirmed to be SCA1. The prevalence ranges from no cases reported in a study among Korean patients [ 51 ] to essentially 100% of all patients in an Eastern Siberian study, where SCA1 was the only type of ADCA identified in the ethnic Sakha population [ 52 ].…”
Section: Sca1mentioning
confidence: 99%
“…A large variance exists in the number of individuals with ADCAs that are confirmed to be SCA1. The prevalence ranges from no cases reported in a study among Korean patients [ 51 ] to essentially 100% of all patients in an Eastern Siberian study, where SCA1 was the only type of ADCA identified in the ethnic Sakha population [ 52 ].…”
Section: Sca1mentioning
confidence: 99%
“…Prevalence of SCA3/MJD in the Azores archipelago increased between 1981 and 2015 (de Araújo et al 2016) [50]. Similarly, prevalence of SCA1 in the Sakha (Yakut) people of Eastern Siberia increased between 1994 and 2013 (Platonov et al 2016) [51].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the fitness of polyQs have shown mixed results. Fitness in SCA1 was estimated to be increased 69 or unchanged 70 while increased fitness was reported in SCA3/MJD 71 and in SCA2 16 . Studies on HD have described increased fitness 69 in one study and unchanged fitness in another, 72 but the latter was performed prior to HD gene discovery.…”
Section: Discussionmentioning
confidence: 99%